2012
DOI: 10.1016/j.bpj.2012.04.037
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminus of Troponin T Is Essential for Maintaining the Inactive State of Regulated Actin

Abstract: Striated muscle contraction is regulated by the actin binding proteins tropomyosin and troponin. Defects in these proteins lead to myopathies and cardiomyopathies. Deletion of the 14 C-terminal residues of cardiac troponin T leads to hypertrophic cardiomyopathy. We showed earlier that regulated actin containing Δ14 TnT was more readily activated than wild-type regulated actin. We suggested that the equilibria among the inactive (blocked), intermediate (closed or calcium), and active (open or myosin) states was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 44 publications
11
69
0
Order By: Relevance
“…Takeda et al [21] speculated that hcTnT R278 might be located within a Ca 2+ -sensitive interface between TnT and Tm, although experimental evidence indicates that removal of TnT’s C-terminus does not affect TnT-Tm binding [70] and that the two Tm-binding regions of TnT are located elsewhere [71]. The C-terminus of cTnT is involved in some form of interaction with other components of the thin filament as removal of the last fourteen amino acids—including R278—negatively affects Ca 2+ regulation of actomyosin function [72,73] and leads to FHC [74]. An alternative hypothesis is that TnT (residues 272–288) normally interacts with actin in the Ca 2+ free state.…”
Section: Discussionmentioning
confidence: 99%
“…Takeda et al [21] speculated that hcTnT R278 might be located within a Ca 2+ -sensitive interface between TnT and Tm, although experimental evidence indicates that removal of TnT’s C-terminus does not affect TnT-Tm binding [70] and that the two Tm-binding regions of TnT are located elsewhere [71]. The C-terminus of cTnT is involved in some form of interaction with other components of the thin filament as removal of the last fourteen amino acids—including R278—negatively affects Ca 2+ regulation of actomyosin function [72,73] and leads to FHC [74]. An alternative hypothesis is that TnT (residues 272–288) normally interacts with actin in the Ca 2+ free state.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, there is a controversy on the definition of the T2 domain (Katrukha, 2013). One group claims that the T2 domain spans residues 197-239 of TnT, corresponding to part of the IT arm (Jin and Chong, 2010), whereas other groups designate the last 16 residues of TnT as T2 (Franklin et al, 2012;Tanokura et al, 1982;Morris and Lehrer, 1984). Although the former idea is consistent with the "inverted" model, we argue that the last 16 residues of TnT forms the T2/TnT hook, which strongly binds to tropomyosin as it runs between the two helices of tropomyosin ( Fig.…”
Section: Comparison With the Previous Model Of Troponinmentioning
confidence: 99%
“…Binding studies of TnT2 have shown that both 51,52 the region N-terminal 53 and C-terminal 54 to the IT arm (cTnT 225 - 276 ) contribute to the interaction with tropomyosin, suggesting that the IT arm is rigidly fixed to tropomyosin. The C-terminus of cTnT, cTnT 275 - 288 , is also immediately adjacent to the cTnI1 28–147 inhibitory region, and both are essential for maintaining the blocked state of actin-tropomyosin 55 . On the other hand, one group has reported that the region corresponding to cTnT1 82 - 2 1 5 interacts with actin and contributes to the activation of actomyosin ATPase 56 .…”
Section: Structure and Function Of Cardiac Troponin C Within The Tropmentioning
confidence: 99%